Ficolins and the Recognition of Pathogenic Microorganisms: An Overview of the Innate Immune Response and Contribution of Single Nucleotide Polymorphisms - Stefan Bidula; Darren W. Sexton; Silke Schelenz (Journal of Immunology Research)
Ficolins are innate pattern recognition receptors (PRR) and play integral roles within the innate immune response to numerous pathogens throughout the circulation, as well as within organs. Pathogens are primarily removed by direct opsonisation following the recognition of cell surface carbohydrates and other immunostimulatory molecules or via the activation of the lectin complement pathway, which results in the deposition of C3b and the recruitment of phagocytes. In recent years, there have been a number of studies implicating ficolins in the recognition and removal of numerous bacterial, viral, fungal, and parasitic pathogens. Moreover, there has been expanding evidence highlighting that mutations within these key immune proteins, or the possession of particular haplotypes, enhance susceptibility to colonization by pathogens and dysfunctional immune responses. This review will therefore encompass previous knowledge on the role of ficolins in the recognition of bacterial and viral pathogens, while acknowledging the recent advances in the immune response to fungal and parasitic infections. Additionally, we will explore the various genetic susceptibility factors that predispose individuals to infection.